2009
DOI: 10.1016/j.ophtha.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and Systemic Autoimmunity after Successful Tumor-Infiltrating Lymphocyte Immunotherapy for Recurrent, Metastatic Melanoma

Abstract: Objective To describe the ophthalmic and systemic autoimmune findings after successful adoptive cell transfer of ex vivo expanded, autologous tumor-reactive tumor-infiltrating lymphocytes (TIL) for metastatic melanoma. Design Retrospective, interventional case report. Participant A 35-year-old man who underwent immunotherapy for metastatic melanoma with adoptive cell transfer of tumor-reactive TIL. Methods A 35-year-old man with metastatic melanoma was treated with TIL plus interleukin-2 (IL-2) therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 30 publications
1
66
2
1
Order By: Relevance
“…This structure of the eye was clearly thickened compared with the mice receiving pmel T cells alone. These findings are similar to recently published data on uveitis in a mouse model and a cutaneous melanoma patient who was treated with immunotherapy (22,23). Importantly, treatment with ACT and peptide vaccination caused a significant delay in B16 melanoma outgrowth in the eye compared with naïve mice (Fig.…”
Section: In Vivo Effector Functions Of Transferred T Cellssupporting
confidence: 91%
See 1 more Smart Citation
“…This structure of the eye was clearly thickened compared with the mice receiving pmel T cells alone. These findings are similar to recently published data on uveitis in a mouse model and a cutaneous melanoma patient who was treated with immunotherapy (22,23). Importantly, treatment with ACT and peptide vaccination caused a significant delay in B16 melanoma outgrowth in the eye compared with naïve mice (Fig.…”
Section: In Vivo Effector Functions Of Transferred T Cellssupporting
confidence: 91%
“…Enriched spleen cells (3 × 10 6 CD8 + T lymphocytes) were adoptively transferred by injection into the tail vein. Mice were immunized 1 day later by shaving the left flank and s.c. injecting 150 μg of homologous human gp100 20-39 KVP (AVGALKVPRNQDWLGVPRQL) or mouse gp100 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] EGS (AVGALEGSRNQDWLGVPRQL) peptide solved in PBS. Toll-like receptor (TLR) ligands were simultaneously applied: 60 mg of Aldara cream containing 5% imiquimod on the skin at the injection site or 25 μg of CpG 1826 from the Leiden Institute of Chemistry.…”
Section: Adoptive Cell Transfer and Immunization Of Micementioning
confidence: 99%
“…Tumor regression without induction of autoimmunity has been reported (9, 58, 59) using T cells with relatively low reactivity against tumor antigens; high-avidity T cells are often associated with autoimmunity (6,27,45,59). Our results showed that antitumor activity and autoimmunity are coupled and have a similar kinetic threshold; reducing autoimmunity cannot be accomplished without sacrificing efficacy of tumor killing.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune destruction of melanocytes in the eye (ocular autoimmunity) has been observed both in human (6,27) and mouse (26) melanoma ACT. To determine whether autoimmunity correlates with TCR antitumor activities, we selected five TCRs showing various antitumor activities (high, L2G2 and R6C12; intermediate, K4H5 and 5CE2; and low, W2C8; Fig.…”
Section: Was Correlated With Tcr Avidity (C) or Affinity (D) (E And F)mentioning
confidence: 99%
See 1 more Smart Citation